Antiplatelet efficacy of ticagrelor versus clopidogrel in Mediterranean patients with diabetes mellitus and chronic coronary syndromes: A crossover pharmacodynamic investigation - Marcano, Ana Lucrecia; Gracida, Montserrat; Roura, Gerard; Gomez-Lara, Josep; Romaguera, Rafael; Teruel, Luis; Fuentes, Lara; Muntané-Carol, Guillem; Meroño, Oona; Sosa, Silvia Gabriela; Gómez-Hospital, Joan Antoni; Comin-Colet, Josep; et al. (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Patients with diabetes mellitus (DM) have augmented platelet reactivity and diminished responsiveness to clopidogrel. Ticagrelor, a more potent P2Y12 inhibitor, is clinically superior to clopidogrel in acute coronary syndromes, although its role in chronic coronary syndromes is still a matter of debate. The aim of this investigation was to compare the pharmacodynamic effectiveness of ticagrelor and clopidogrel in Mediterranean DM patients with stable coronary artery disease (CAD). Methods: In this prospective, randomized, crossover study, patients (n=20) were randomized (1:1) to receive, on top of aspirin therapy, either ticagrelor 180 mg loading dose (LD) / 90mg maintenance dose (MD) b.i.d. or clopidogrel 600 mg LD / 75 mg MD o.d. for one week in a crossover fashion with a 2–4 week washout period between regimens. Platelet function measurements were performed at 4 timepoints in each period (baseline, 2 and 24 hours after LD, and 1 week), including light transmission aggregometry (LTA, primary endpoint), VASP assay, Multiplate and VerifyNow P2Y12. Results: The ticagrelor LD achieved greater platelet inhibitory effect, measured with LTA (20μM ADP as agonist), than clopidogrel at 2 hours (34.9±3.9% vs. 63.6±3.9%; p<0.001) and 24 hours (39.4±3.5% vs. 52.3±3.8%; p=0.014). After 1 week of therapy, platelet aggregation was again significantly lower with ticagrelor compared to clopidogrel (30.7±3.0% vs. 54.3±3.0%; p<0.001). The results were consistent with the other platelet function assays used. Conclusions: In Mediterranean patients with DM and stable CAD, ticagrelor achieves a more potent antiplatelet effect than clopidogrel after the LD and during the maintenance phase of therapy.